Pengetahuan tentang Stroke, Faktor Risiko, Tanda Peringatan Stroke, dan Respon Mencari Bantuan pada Pasien Stroke Iskemik - Fitria Handayani (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2019)
Among stroke ischemic survivor, disability was contributed the stroke prevention and respon in medical treatment engagement when onset. Prevention stroke also was influenced the stroke knowledge. Stroke konowledge invarious population have studied. Meanwhile the the knowledge of stroke, risk factor, symtom warning stroke, and respon to medical treatment engagement was not established in Indonesia. The aim of the study was to investigate the stroke knowledge among stroke ischemic survivor. Method was descriptive study. The sample were 78 samples. Quetionaire was Stroke Knowledge Test (SKT). Ethic was conducted by Ethic Committe of Medical Faculty Diponegoro University. The Result Showed that the knowledge of stroke, risk factor, symtom warning stroke, and respon to medical treatment engagement were poor. This result gain the good insight in developing nursing intervention.